Abrasive agent for cleaning waste plastics as well as preparation method and application of abrasive agent
By using zirconia microbeads and modified nano iron tetroxide as friction medium in waste plastic cleaning equipment, the problem of complex and poor cleaning effect of existing equipment is solved, and the cleaning effect of efficiently removing contaminants and impurities is achieved, and recycled plastic with excellent performance is obtained.
Patent Information
- Application Number
- CN202411962251.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Existing waste plastic cleaning equipment is complex and has poor cleaning effect, and it is especially difficult to effectively remove pollutants and impurities with strong adhesion.
Zirconia microbeads are used as friction medium, and sheet-shaped nano-ferrous tetroxide is modified on its surface, and the strong friction force of the microbeads and the scratching and magnetic adsorption force of the nano-ferrous tetroxide are used for cleaning.
It greatly improves the cleaning efficiency of waste plastic sheets, can effectively remove paint and impurities on the plastic surface, and adsorb and remove metal impurities, obtaining recycled plastic products with excellent performance without complex cleaning equipment.
Smart Images

Figure BDA0005217465800000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste plastic recycling, and in particular to a friction agent for cleaning waste plastics, and a preparation method and application thereof. Background Art
[0002] Compared with metals and inorganic non-metallic materials, plastics are easy to process and manufacture, light in weight, stable in performance, low in manufacturing cost, and highly plastic, and are therefore widely used in packaging, building materials, daily chemicals, and other fields. Directly discarding waste plastic products after consumption will cause environmental pollution and waste of resources. If they can be effectively recycled and reused, and low-value waste plastic products can be transformed into high-value-added recycled plastic products, it will not only reduce the environmental burden but also effectively promote the recycling of waste plastics. There will be many pollutants with strong adhesion on the surface of plastic products after consumption. If they are not cleaned properly, they will remain in the recycled plastic during the later processing process, which will have a great negative impact on its overall performance and limit its back-end application.
[0003] Patent CN 115648485 A discloses a plastic product recycling and cleaning device and a cleaning method thereof, and relates to a plastic product recycling and cleaning device, including an abrasive washing tank, a conveying device, a cleaning frame and an abrasive supply device, wherein the conveying device is used to input the cleaning frame into the abrasive washing tank and output it out of the abrasive washing tank; a first impact assembly is installed in the abrasive washing tank, and the first impact assembly includes an ascending impact member, a first driving part for driving the ascending impact member to rise and fall, a descending impact member and a second driving part for driving the descending impact member to rise and fall, and the cleaning frame passes between the ascending impact member and the descending impact member; a through hole for the ascending impact member to pass through is provided at the bottom of the cleaning frame; and the abrasive supply device is used to convey the abrasive into the cleaning frame. Plastic products and abrasives are successively placed into the cleaning frame, and the cleaning frame is impacted by the first impact assembly to loosen the dirt. After the dirt is loosened, the impact force combined with the huge friction force generated by the abrasive takes the dirt away, and the dirt is first loosened before the large friction force is generated to achieve efficient and high-quality cleaning of plastic products. This patent uses an impact component to impact plastic products to loosen dirt, and then removes the dirt through friction. This method has high requirements for equipment, and the impact will not produce much cleaning effect on some impurities with strong adhesion, such as paint.
[0004] Patent CN 218890928 U discloses a recyclable plastic scrap cleaning device, which belongs to the technical field of scrap processing equipment, including a cleaning drum, a plurality of water filter holes are arranged below the cleaning drum, a driving mechanism is arranged inside the cleaning drum, an anti-blocking component is arranged inside the cleaning drum and between the driving mechanism and the water filter hole, and a guide pipe is connected to the top of the cleaning drum; the utility model is provided with an anti-blocking component, during the cleaning process, the filter screen can prevent the plastic scraps from falling into the water filter hole, causing the water filter hole to be blocked, the vibration generated by the operation of the vibrator is transmitted to the installation box, and then transmitted to the filter screen through the installation box, so that the filter screen vibrates, and the cleaning water mixed with the plastic scraps on the filter screen is accelerated to fall, and during the falling process, part of the cleaning water falls on the water guide cover, falls along the water guide cover, and is discharged through the water filter hole together with the cleaning water falling at other positions. Although this drum cleaning device can increase the contact area between the cleaning water and the plastic and improve the cleaning efficiency, it cannot effectively remove impurities with strong adsorption. Summary of the invention
[0005] Aiming at the problems of complicated waste plastic cleaning equipment and poor cleaning effect, the present invention provides a method for preparing a friction agent for cleaning waste plastic. Zirconia microbeads are used as friction medium, and flaky nano-ferroferric oxide is loaded on the surface of the microbeads to increase the scraping effect on the surface of recycled plastic. Recycled plastic products with excellent performance can be obtained in ordinary cleaning equipment through the friction medium.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a friction agent for cleaning waste plastics, comprising the steps of:
[0008] Step 1, mixing zirconium oxide microbeads of at least two particle sizes and an alkaline dopamine solution, letting the mixture stand, taking it out, washing and drying it to obtain dopamine-modified zirconium oxide microbeads;
[0009] Step 2, mixing dopamine-modified zirconia microbeads, a trivalent iron source, a metal salt, water and a solvent and standing the mixture to obtain Fe2O3 nanosheet-modified zirconia microparticles through an alcohol-thermal reaction;
[0010] Step 3: subjecting the Fe2O3 nanosheet-modified zirconia particles to a reduction reaction in a tubular furnace to obtain Fe3O4 nanosheet-modified zirconia particles.
[0011] In the present invention, zirconium beads of different particle sizes are added as friction media. During the stirring process, the strong friction between the micro-beads and the plastic crushed pieces can effectively remove pollutants and foreign matter on the plastic surface. In order to further increase the friction between the zirconium beads and the plastic crushed pieces, flaky nano-ferroferric oxide is modified on the surface of the micro-beads. During the cleaning process, the flaky nano-ferroferric oxide scrapes the plastic crushed pieces as the zirconium beads roll, which can effectively remove paint and other impurities on the surface of the plastic crushed pieces. At the same time, the nano-ferroferric oxide has a certain magnetism and can effectively absorb metal foreign matter or metal fines mixed inside the plastic crushed pieces. Under the combined effect, the cleaning efficiency of the discarded plastic pieces is greatly improved, and there is no need to equip large and complex cleaning equipment.
[0012] In step 1, the zirconium oxide microbeads have a particle size of 0.01-6 mm; the particle size difference of zirconium oxide microbeads of different particle sizes is 0.05-5 mm; preferably, the zirconium oxide microbeads are a combination of particle sizes of 0.5 mm, 1.5 mm and 5 mm. The reasonable ratio of zirconium oxide microbeads of different particle sizes can effectively fill the gap between them and the plastic crushed pieces of different particle sizes, thereby effectively increasing the contact area and improving the friction efficiency.
[0013] Further preferably, the mass ratio of the microbeads with particle sizes of 0.5 mm, 1.5 mm and 5 mm in the zirconium oxide microbeads is 5 to 15: 20 to 40: 40 to 60. The zirconium oxide microbeads with different particle sizes are matched with each other in a certain mass ratio, which can effectively rub the surfaces, edges and other parts of the plastic crushed pieces with different particle sizes to achieve deep cleaning.
[0014] The molar concentration of dopamine in the alkaline dopamine solution is 0.001-1 mol / L; the pH of the solution is adjusted to 8-10 by adding tris buffer; under alkaline conditions, dopamine can be more fully polymerized and wrapped on the surface of the zirconium oxide microbeads.
[0015] The mass ratio of dopamine to zirconium oxide microbeads is 1-5:100.
[0016] The standing in step 1 is standing at 10-40° C. for 10-30 hours.
[0017] The ferric iron source includes one or more of ferric nitrate, ferric sulfate, ferric chloride and ferric bromide;
[0018] The metal salt includes one or more of sodium acetate, sodium carbonate, sodium bicarbonate, potassium acetate, potassium carbonate, and potassium bicarbonate, which are used to adjust the pH value of the solution;
[0019] In step 2, the solvent includes one or more of methanol, ethanol and n-propanol.
[0020] The mass ratio of the dopamine-modified zirconium oxide microbeads, the trivalent iron source and the metal salt is 3-20:0.5-10:1-10;
[0021] The molar ratio of water to iron ions in the ferric iron source is (10-100):1; the molar ratio of water to iron ions will regulate the morphology of Fe2O3 nanosheets. Preferably, the molar ratio of water to iron ions in the ferric iron source is (10-30):1;
[0022] The mass ratio of the solvent to the dopamine-modified zirconium oxide microbeads is 1 to 5:1.
[0023] In step 2, the mixture is allowed to stand at 10-40° C. for 12-36 hours; the alcohol thermal reaction is carried out at 160-200° C. for 12-24 hours.
[0024] The reduction reaction in step 3 is carried out at 400-600° C. for 2-8 hours in a hydrogen atmosphere.
[0025] The invention also provides a friction agent for cleaning waste plastics prepared by the preparation method.
[0026] The present invention also provides a method for cleaning waste plastics, comprising the steps of: stirring the abrasive, waste plastic fragments and water in a stirrer, taking out the plastic fragments after the stirring, cleaning with clean water and drying to obtain recycled plastics.
[0027] The mass of the friction agent is 20-60% of the waste plastic fragments;
[0028] Preferably, the stirring speed is 30-100 r / min, and the stirring time is at least 20 min.
[0029] The cleaning equipment uses an ordinary stainless steel agitator.
[0030] Preferably, after the stirring is completed, the plastic crushed pieces are taken out, and a certain amount of calcium chloride can be added to adjust the density of the aqueous solution. The amount of calcium chloride is determined according to the density of the plastic crushed material to ensure that the density of the aqueous solution is greater than the density of the plastic crushed material and less than the density of the cleaning agent. Thus, the purpose of separating the plastic crushed material and the cleaning agent through the aqueous solution is achieved. The waste plastic crushed pieces include but are not limited to plastic waste crushed pieces made of materials such as polysulfone, polyetheretherketone, polyphenylene sulfide, polyimide and polybenzimidazole.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) In the present invention, zirconium oxide microbeads are used as friction media, and the strong friction force of microbeads of different particle sizes is used to remove pollutants and foreign matter on the surface of the plastic fragments. Reduced ferroferric oxide nanosheets are modified on the surface of the microbeads. The nanosheets can not only use the scraping force of the nanosheets like a blade, but also use the magnetic adsorption of ferroferric oxide to remove metal impurities, thereby greatly improving the cleaning effect of the plastic fragments.
[0033] (2) In the present invention, the zirconium oxide microbeads modified with ferrosoferric oxide nanosheets and the waste plastic fragments are cleaned by ordinary stirring and mixing, and no complicated cleaning equipment is required to achieve an efficient cleaning effect, and the mechanical properties of the recycled plastic products are good. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0035] The raw materials used in the following specific embodiments are all purchased from the market.
[0036] Example 1 (particle size ratio: 15:30:55)
[0037] Prepare 1000 portions of 0.01 mol / L dopamine solution, add 100 portions of zirconium oxide microbeads of different particle sizes (0.5 mm: 1.5 mm: 5 mm = 15:30:55) to the dopamine solution, add tris buffer to adjust the solution pH to 9, and remove the zirconium oxide microbeads after standing at room temperature for 24 hours. Wash with water and ethanol three times respectively, and place in an oven for drying.
[0038] Take 20 parts of the above zirconia microbeads and add them to 45 parts of ethanol solution, add 10 parts of FeCl3, 10 parts of sodium acetate and an appropriate amount of water (the molar ratio of water to iron ions in the trivalent iron source is 20:1), stir and mix evenly, and let stand at room temperature (25°C) for 24 hours to obtain a mixed solution. Pour all the prepared mixed solution into a stainless steel reactor, then raise the temperature to 170°C and react for 12 hours. After the reaction is completed, the zirconia microbeads are removed, washed with ethanol and water three times respectively, and finally dried to obtain Fe2O3 nanosheet-modified zirconia microbeads.
[0039] The Fe2O3 nanosheets modified zirconia microbeads were subjected to high temperature reduction (600°C, 8h, H25sccm, Ar 95sccm) in a CVD tube furnace to transform the Fe2O3 nanosheets into magnetic Fe3O4 nanosheets, and finally the Fe3O4 nanosheets modified zirconia microbeads were obtained.
[0040] Take 50 parts of Fe3O4 nanosheet-modified zirconium oxide microbeads, 100 parts of polysulfone (PPSU) baby bottle broken pieces, and 300 parts of water, add them into a stainless steel agitator and start stirring, stirring time 40min, rotating speed 50r / min. The stirred mixture is added into a 30% CaCl2 aqueous solution, the polysulfone broken pieces on the surface are fished out, then cleaned with clean water, and used for extrusion granulation after drying. The cleaned polysulfone broken pieces are added into a twin-screw extruder for granulation extrusion, the extrusion temperature is 300 / 310 / 320 / 340 / 350 / 350 / 350 / 350 / 340℃, the rotating speed is 300rpm, and finally the regenerated polysulfone particles are obtained.
[0041] Example 2 (particle size ratio: 10:35:55)
[0042] Prepare 1000 portions of 0.01 mol / L dopamine solution, add 100 portions of zirconium oxide microbeads of different particle sizes (0.5 mm: 1.5 mm: 5 mm = 10:35:55) to the dopamine solution, add tris buffer to adjust the solution pH to 10, and remove the zirconium oxide microbeads after standing at room temperature for 10 hours. Wash with water and ethanol three times respectively, and place in an oven for drying.
[0043] Take 20 parts of the above zirconia microbeads and add them to 30 parts of ethanol solution, add 10 parts of FeCl3, 10 parts of sodium acetate and an appropriate amount of water (the molar ratio of water to iron ions in the trivalent iron source is 20:1), stir and mix evenly, and let stand at room temperature (25°C) for 24 hours to obtain a mixed solution. Pour all the prepared mixed solution into a stainless steel reactor, then raise the temperature to 170°C and react for 12 hours. After the reaction is completed, the zirconia microbeads are removed, washed with ethanol and water three times respectively, and finally dried to obtain Fe2O3 nanosheet-modified zirconia microbeads.
[0044] The Fe2O3 nanosheets modified zirconia microbeads were subjected to high temperature reduction (600°C, 8h, H25sccm, Ar 95sccm) in a CVD tube furnace to transform the Fe2O3 nanosheets into magnetic Fe3O4 nanosheets, and finally the Fe3O4 nanosheets modified zirconia microbeads were obtained.
[0045] Take 50 parts of Fe3O4 nanosheet-modified zirconium oxide microbeads, 100 parts of PPSU baby bottle crushed flakes, and 300 parts of water and add them to a stainless steel agitator and start stirring for 40 minutes at a speed of 50r / min. Add the stirred mixture to a 30% CaCl2 aqueous solution, remove the polysulfone crushed flakes on the surface, then wash them with clean water, and use them for extrusion granulation after drying. Add the washed polysulfone crushed flakes to a twin-screw extruder for granulation extrusion, with an extrusion temperature of 300 / 310 / 320 / 340 / 350 / 350 / 350 / 350 / 340°C and a rotation speed of 300rpm to finally obtain regenerated polysulfone particles.
[0046] Example 3 (particle size ratio: 5:35:60)
[0047] Prepare 1000 portions of 0.01 mol / L dopamine solution, add 100 portions of zirconium oxide microbeads of different particle sizes (0.5 mm: 1.5 mm: 5 mm = 5:35:60) to the dopamine solution, add tris buffer to adjust the solution pH to 9.5, and remove the zirconium oxide microbeads after standing at room temperature for 24 hours. Wash with water and ethanol three times respectively, and place in an oven for drying.
[0048] Take 20 parts of the above zirconium oxide microbeads and add them to 60 parts of ethanol solution, add 10 parts of trivalent FeCl3, 10 parts of sodium acetate and an appropriate amount of water (the molar ratio of water to iron ions in the trivalent iron source is 20:1), stir and mix evenly, and let stand at room temperature (25°C) for 24 hours to obtain a mixed solution. Pour all the prepared mixed solution into a stainless steel reactor, then raise the temperature to 200°C and react for 18 hours. After the reaction is completed, the zirconium oxide microbeads are washed 3 times with ethanol and water respectively, and finally dried to obtain Fe2O3 nanosheet-modified zirconium oxide microbeads.
[0049] The Fe2O3 nanosheets modified zirconia microbeads were subjected to high temperature reduction (600°C, 8h, H25sccm, Ar 95sccm) in a CVD tube furnace to transform the Fe2O3 nanosheets into magnetic Fe3O4 nanosheets, and finally the Fe3O4 nanosheets modified zirconia microbeads were obtained.
[0050] Take 50 parts of Fe3O4 nanosheet-modified zirconium oxide microbeads, 100 parts of PPSU baby bottle crushed flakes, and 300 parts of water and add them to a stainless steel agitator and start stirring for 40 minutes at a speed of 50r / min. Add the stirred mixture to a 30% CaCl2 aqueous solution, remove the polysulfone crushed flakes on the surface, then wash them with clean water, and use them for extrusion granulation after drying. Add the washed polysulfone crushed flakes to a twin-screw extruder for granulation extrusion, with an extrusion temperature of 300 / 310 / 320 / 340 / 350 / 350 / 350 / 350 / 340°C and a rotation speed of 300rpm to finally obtain regenerated polysulfone particles.
[0051] Example 4 (FeCl3 content)
[0052] Prepare 1000 portions of 0.01 mol / L dopamine solution, add 100 portions of zirconium oxide microbeads of different particle sizes (0.1 mm: 1.5 mm: 5 mm = 15:30:55) to the dopamine solution, add tris buffer to adjust the solution pH to 9, and remove the zirconium oxide microbeads after standing at room temperature for 18 hours. Wash with water and ethanol three times respectively, and place in an oven for drying.
[0053] Take 20 parts of the above zirconia microbeads and add them to 45 parts of ethanol solution, add 7 parts of trivalent FeCl3, 10 parts of sodium acetate and an appropriate amount of water (the molar ratio of water to iron ions in the trivalent iron source is 20:1), stir and mix evenly, and let stand at room temperature (25°C) for 24 hours to obtain a mixed solution. Pour all the prepared mixed solution into a stainless steel reactor, then raise the temperature to 180°C and react for 24 hours. After the reaction is completed, the zirconia microbeads are removed, washed with ethanol and water three times respectively, and finally dried to obtain Fe2O3 nanosheet-modified zirconia microbeads.
[0054] The Fe2O3 nanosheets modified zirconia microbeads were subjected to high temperature reduction (600°C, 8h, H25sccm, Ar 95sccm) in a CVD tube furnace to transform the Fe2O3 nanosheets into magnetic Fe3O4 nanosheets, and finally the Fe3O4 nanosheets modified zirconia microbeads were obtained.
[0055] Take 50 parts of Fe3O4 nanosheet-modified zirconium oxide microbeads, 100 parts of PPSU baby bottle crushed flakes, and 300 parts of water and add them to a stainless steel agitator and start stirring for 40 minutes at a speed of 50r / min. Add the stirred mixture to a 30% CaCl2 aqueous solution, remove the polysulfone crushed flakes on the surface, then wash them with clean water, and use them for extrusion granulation after drying. Add the washed polysulfone crushed flakes to a twin-screw extruder for granulation extrusion, with an extrusion temperature of 300 / 310 / 320 / 340 / 350 / 350 / 350 / 350 / 340°C and a rotation speed of 300rpm to finally obtain regenerated polysulfone particles.
[0056] Example 5 (FeCl3 content)
[0057] Prepare 1000 portions of 0.01 mol / L dopamine solution, add 100 portions of zirconium oxide microbeads of different particle sizes (0.5 mm: 1.5 mm: 5 mm = 15:30:55) to the dopamine solution, add tris buffer to adjust the solution pH to 8.5, let stand at room temperature for 12 hours, remove the zirconium oxide beads, wash with water and ethanol three times respectively, and place in an oven for drying.
[0058] Take 20 parts of the above zirconia beads and add them to 50 parts of ethanol solution, add 4 parts of trivalent FeCl3, 10 parts of sodium acetate and an appropriate amount of water (the molar ratio of water to iron ions in the trivalent iron source is 20:1), stir and mix evenly, and let stand at room temperature (25°C) for 24 hours to obtain a mixed solution. Pour all the prepared mixed solution into a stainless steel reactor, then increase the temperature to 190°C and react for 12 hours. After the reaction is completed, the zirconia microbeads are fished out, washed 3 times with ethanol and water respectively, and finally dried to obtain Fe2O3 nanosheet-modified zirconia microbeads.
[0059] The Fe2O3 nanosheets modified zirconia microbeads were subjected to high temperature reduction (600°C, 8h, H25sccm, Ar 95sccm) in a CVD tube furnace to transform the Fe2O3 nanosheets into magnetic Fe3O4 nanosheets, and finally the Fe3O4 nanosheets modified zirconia microbeads were obtained.
[0060] Take 50 parts of Fe3O4 nanosheet-modified zirconium oxide microbeads, 100 parts of PPSU baby bottle crushed flakes, and 300 parts of water and add them to a stainless steel agitator and start stirring for 40 minutes at a speed of 50r / min. Add the stirred mixture to a 30% CaCl2 aqueous solution, remove the polysulfone crushed flakes on the surface, then wash them with clean water, and use them for extrusion granulation after drying. Add the washed polysulfone crushed flakes to a twin-screw extruder for granulation extrusion, with an extrusion temperature of 300 / 310 / 320 / 340 / 350 / 350 / 350 / 350 / 340°C and a rotation speed of 300rpm to finally obtain regenerated polysulfone particles.
[0061] Example 6 (Water Content)
[0062] Prepare 1000 portions of 0.01 mol / L dopamine solution, add 100 portions of zirconium oxide microbeads of different particle sizes (0.5 mm: 1.5 mm: 5 mm = 15:30:55) to the dopamine solution, add tris buffer to adjust the solution pH to 9, and remove the zirconium oxide microbeads after standing at room temperature for 24 hours. Wash with water and ethanol three times respectively, and place in an oven for drying.
[0063] Take 20 parts of the above zirconium oxide microbeads and add them to 45 parts of ethanol solution, add 10 parts of FeCl3, 10 parts of sodium acetate and an appropriate amount of water (the molar ratio of water to iron ions in the trivalent iron source is 10:1), stir and mix evenly, and let stand at room temperature (25°C) for 24 hours to obtain a mixed solution. Pour all the prepared mixed solution into a stainless steel reactor, then raise the temperature to 170°C and react for 12 hours. After the reaction is completed, the zirconium oxide microbeads are removed, washed with ethanol and water three times respectively, and finally dried to obtain Fe2O3 nanosheet-modified zirconium oxide microbeads.
[0064] The Fe2O3 nanosheets modified zirconia microbeads were subjected to high temperature reduction (600°C, 8h, H25sccm, Ar 95sccm) in a CVD tube furnace to transform the Fe2O3 nanosheets into magnetic Fe3O4 nanosheets, and finally the Fe3O4 nanosheets modified zirconia microbeads were obtained.
[0065] Take 50 parts of Fe3O4 nanosheet-modified zirconium oxide microbeads, 100 parts of PPSU baby bottle crushed flakes, and 300 parts of water and add them to a stainless steel agitator and start stirring for 40 minutes at a speed of 50r / min. Add the stirred mixture to a 30% CaCl2 aqueous solution, remove the polysulfone crushed flakes on the surface, then wash them with clean water, and use them for extrusion granulation after drying. Add the washed polysulfone crushed flakes to a twin-screw extruder for granulation extrusion, with an extrusion temperature of 300 / 310 / 320 / 340 / 350 / 350 / 350 / 350 / 340°C and a rotation speed of 300rpm to finally obtain regenerated polysulfone particles.
[0066] Example 7 (Water Content)
[0067] Prepare 1000 portions of 0.01 mol / L dopamine solution, add 100 portions of zirconium oxide microbeads of different particle sizes (0.5 mm: 1.5 mm: 5 mm = 15:30:55) to the dopamine solution, add tris buffer to adjust the solution pH to 9, and remove the zirconium oxide microbeads after standing at room temperature for 24 hours. Wash with water and ethanol three times respectively, and place in an oven for drying.
[0068] Take 20 parts of the above zirconia microbeads and add them to 45 parts of ethanol solution, add 10 parts of FeCl3, 10 parts of sodium acetate and an appropriate amount of water (the molar ratio of water to iron ions in the trivalent iron source is 2:1), stir and mix evenly, and let stand at room temperature (25°C) for 24 hours to obtain a mixed solution. Pour all the prepared mixed solution into a stainless steel reactor, then raise the temperature to 170°C and react for 12 hours. After the reaction is completed, the zirconia microbeads are removed, washed with ethanol and water three times respectively, and finally dried to obtain Fe2O3 nanosheet-modified zirconia microbeads.
[0069] The Fe2O3 nanosheets modified zirconia microbeads were subjected to high temperature reduction (600°C, 8h, H25sccm, Ar 95sccm) in a CVD tube furnace to transform the Fe2O3 nanosheets into magnetic Fe3O4 nanosheets, and finally the Fe3O4 nanosheets modified zirconia microbeads were obtained.
[0070] Take 50 parts of Fe3O4 nanosheet-modified zirconium oxide microbeads, 100 parts of PPSU baby bottle crushed flakes, and 300 parts of water and add them to a stainless steel agitator and start stirring for 40 minutes at a speed of 50r / min. Add the stirred mixture to a 30% CaCl2 aqueous solution, remove the polysulfone crushed flakes on the surface, then wash them with clean water, and use them for extrusion granulation after drying. Add the washed polysulfone crushed flakes to a twin-screw extruder for granulation extrusion, with an extrusion temperature of 300 / 310 / 320 / 340 / 350 / 350 / 350 / 350 / 340°C and a rotation speed of 300rpm to finally obtain regenerated polysulfone particles.
[0071] Comparative Example 1 (without Fe3O4)
[0072] Add 50 parts of zirconium oxide microbeads of different particle sizes (0.5mm: 1.5mm: 5mm = 15:30:55), 100 parts of PPSU baby bottle flakes, and 300 parts of water into a stainless steel agitator and start stirring for 40 minutes at a speed of 50r / min. Add the stirred mixture into a 30% CaCl2 aqueous solution, remove the polysulfone flakes on the surface, wash them with clean water, and use them for extrusion granulation after drying. Add the washed PPSU flakes into a twin-screw extruder for granulation extrusion at a temperature of 300 / 310 / 320 / 340 / 350 / 350 / 350 / 350 / 340°C and a speed of 300rpm to finally obtain recycled polysulfone particles.
[0073] Comparative Example 2 (single particle size)
[0074] Prepare 1000 parts of 0.01 mol / L dopamine solution, add 100 parts of 0.5 mm zirconium oxide microbeads to the dopamine solution, add tris buffer to adjust the solution pH to 9, let stand at room temperature for 24 hours, remove the zirconium oxide microbeads, wash with water and ethanol three times respectively, and place in an oven for drying.
[0075] Take 20 parts of the above zirconia microbeads and add them to 45 parts of ethanol solution, add 10 parts of FeCl3, 10 parts of sodium acetate and an appropriate amount of water (the molar ratio of water to iron ions in the trivalent iron source is 20:1), stir and mix evenly, and let stand at room temperature (25°C) for 24 hours to obtain a mixed solution. Pour all the prepared mixed solution into a stainless steel reactor, then raise the temperature to 170°C and react for 12 hours. After the reaction is completed, the zirconia microbeads are removed, washed with ethanol and water three times respectively, and finally dried to obtain Fe2O3 nanosheet-modified zirconia microbeads.
[0076] The Fe2O3 nanosheets modified zirconia microbeads were subjected to high temperature reduction (600°C, 8h, H25sccm, Ar 95sccm) in a CVD tube furnace to transform the Fe2O3 nanosheets into magnetic Fe3O4 nanosheets, and finally the Fe3O4 nanosheets modified zirconia microbeads were obtained.
[0077] Take 50 parts of Fe3O4 nanosheet-modified zirconium oxide microbeads, 100 parts of PPSU baby bottle crushed flakes, and 300 parts of water and add them to a stainless steel agitator and start stirring for 40 minutes at a speed of 50r / min. Add the stirred mixture to a 30% CaCl2 aqueous solution, remove the polysulfone crushed flakes on the surface, then wash them with clean water, and use them for extrusion granulation after drying. Add the washed polysulfone crushed flakes to a twin-screw extruder for granulation extrusion, with an extrusion temperature of 300 / 310 / 320 / 340 / 350 / 350 / 350 / 350 / 340°C and a rotation speed of 300rpm to finally obtain regenerated polysulfone particles.
[0078] Comparative Example 3 (single large particle size)
[0079] Prepare 1000 parts of 0.01 mol / L dopamine solution, add 100 parts of 5 mm zirconium oxide microbeads to the dopamine solution, add tris buffer to adjust the solution pH to 9, let stand at room temperature for 24 hours, then remove the zirconium oxide microbeads, wash with water and ethanol three times respectively, and place in an oven for drying.
[0080] Take 20 parts of the above zirconia microbeads and add them to 45 parts of ethanol solution, add 10 parts of FeCl3, 10 parts of sodium acetate and an appropriate amount of water (the molar ratio of water to iron ions in the trivalent iron source is 20:1), stir and mix evenly, and let stand at room temperature (25°C) for 24 hours to obtain a mixed solution. Pour all the prepared mixed solution into a stainless steel reactor, then raise the temperature to 170°C and react for 12 hours. After the reaction is completed, the zirconia microbeads are removed, washed with ethanol and water three times respectively, and finally dried to obtain Fe2O3 nanosheet-modified zirconia microbeads.
[0081] The Fe2O3 nanosheets modified zirconia microbeads were subjected to high temperature reduction (600°C, 8h, H25sccm, Ar 95sccm) in a CVD tube furnace to transform the Fe2O3 nanosheets into magnetic Fe3O4 nanosheets, and finally the Fe3O4 nanosheets modified zirconia microbeads were obtained.
[0082] Take 50 parts of Fe3O4 nanosheet-modified zirconium oxide microbeads, 100 parts of PPSU baby bottle crushed flakes, and 300 parts of water and add them to a stainless steel agitator and start stirring for 40 minutes at a speed of 50r / min. Add the stirred mixture to a 30% CaCl2 aqueous solution, remove the polysulfone crushed flakes on the surface, then wash them with clean water, and use them for extrusion granulation after drying. Add the washed polysulfone crushed flakes to a twin-screw extruder for granulation extrusion, with an extrusion temperature of 300 / 310 / 320 / 340 / 350 / 350 / 350 / 350 / 340°C and a rotation speed of 300rpm to finally obtain regenerated polysulfone particles.
[0083] The recycled polysulfone particles prepared in the embodiment and the comparative example were prepared into test specimens according to GB / T1040-2006 and GB / T1043-2008 standards, and the mechanical properties were tested. For the black spot test, 10 g of particles were taken and visually observed under a 5x magnifying glass, and the size of the black spots was confirmed and the number was counted using a film card for comparison. The test results are shown in Table 1.
[0084] Table 1 Performance of regenerated polysulfone particles in Examples and Comparative Examples
[0085]
[0086] As can be seen from Table 1, compared with Examples 1-3 and Comparative Examples 2-3, the mixture of zirconia microbeads of different particle sizes can significantly improve the mechanical properties of the regenerated polysulfone compared with zirconia microbeads of a single particle size, and the impurity black spots in the regenerated product are also fewer and smaller.
[0087] The results of Examples 1 and 4-5 show that the amount of iron precursor affects the amount of iron nanosheets, and thus also affects the cleaning effect of waste plastics. Comparative Example 1 shows that when there is no scraping effect of Fe3O4 nanosheets, the cleaning effect will be significantly reduced, and the mechanical properties of the recycled products will also be significantly reduced.
[0088] The results of Examples 1 and 6-7 show that the reduction in the amount of water used leads to a higher concentration of iron salts. In the alcohol thermal reaction, the Fe2O3 nanosheets are deposited too quickly and agglomerated, resulting in a decrease in the cleaning effect and affecting the performance of the recycled plastic product.
Claims
1. A method for preparing a friction agent for cleaning waste plastics, characterized in that: Includes steps: Step 1, mixing zirconium oxide microbeads of at least two particle sizes and an alkaline dopamine solution, letting the mixture stand, taking it out, washing and drying it to obtain dopamine-modified zirconium oxide microbeads; Step 2, mixing dopamine-modified zirconia microbeads, a trivalent iron source, a metal salt, water and a solvent, and then standing the mixture, and then subjecting the mixture to an alcohol-heat reaction to obtain Fe2O3 nanosheet-modified zirconia microparticles; Step 3: subjecting the Fe2O3 nanosheet-modified zirconia particles to a reduction reaction in a tubular furnace to obtain Fe3O4 nanosheet-modified zirconia particles.
2. The method for preparing a friction agent for cleaning waste plastics according to claim 1, characterized in that: In step 1, the zirconia microbeads have a particle size of 0.01-6 mm; the particle size difference of zirconia microbeads with different particle sizes is 0.05-5 mm; preferably, the zirconia microbeads are a combination of particle sizes of 0.5 mm, 1.5 mm and 5 mm.
3. The method for preparing a friction agent for cleaning waste plastics according to claim 2, characterized in that: The mass ratio of the microbeads with particle sizes of 0.5 mm, 1.5 mm and 5 mm in the zirconium oxide microbeads is 5-15:20-40:40-60.
4. The method for preparing a friction agent for cleaning waste plastics according to claim 1, characterized in that: The molar concentration of dopamine in the dopamine solution is 0.001 to 1 mol / L; the pH of the solution is adjusted to 8 to 10 by adding tris buffer; and / or, the mass ratio of dopamine to zirconium oxide microbeads is 1-5:100; And / or, the standing in step 1 is standing at 10-40° C. for 10-30 hours.
5. The method for preparing a friction agent for cleaning waste plastics according to claim 1, characterized in that: The ferric iron source includes one or more of ferric nitrate, ferric sulfate, ferric chloride and ferric bromide; And / or, the metal salt includes one or more of sodium acetate, sodium carbonate, sodium bicarbonate, potassium acetate, potassium carbonate, and potassium bicarbonate; and / or, the solvent comprises one or more of methanol, ethanol and n-propanol; And / or, the mass ratio of the dopamine-modified zirconium oxide microbeads, the ferric iron source and the metal salt is 3-20:0.5-10:1-10; And / or, the molar ratio of water to iron ions in the ferric iron source is (10-100):1; And / or, the mass ratio of the solvent to the dopamine-modified zirconia microbeads is 1 to 5:
1.
6. The method for preparing a friction agent for cleaning waste plastics according to claim 1, characterized in that: In step 2, the mixture is allowed to stand at 10-40° C. for 12-36 hours; and the alcohol thermal reaction is carried out at 160-200° C. for 12-24 hours.
7. The method for preparing a friction agent for cleaning waste plastics according to claim 1, characterized in that: The reduction reaction in step 3 is carried out at 400-600° C. for 2-8 hours in a hydrogen atmosphere.
8. A friction agent for cleaning waste plastics obtained according to the preparation method according to any one of claims 1 to 7.
9. A method for cleaning waste plastics, characterized in that: The method comprises the steps of: stirring the friction agent described in claim 8, waste plastic crushed pieces and water in a stirrer, and after stirring, taking out the plastic crushed pieces, washing them with clean water and drying them to obtain recycled plastic.
10. The method for cleaning waste plastics according to claim 9, characterized in that: The mass of the friction agent is 20-60% of the waste plastic fragments; and / or the stirring speed is 30-100 r / min, and the stirring time is at least 20 minutes.
Citation Information
Patent Citations
Ceramic cleaning agent and preparation method thereof
CN109694782A
Recyclable bimetal modified magnetic phosphorus removal adsorbent as well as preparation method and application thereof
CN112090392A
Preparation method of magnetic polydopamine modified CuS nanoparticles with high solar energy absorption
CN115611347A
Method for removing metal ions in organic matter by using magnetic zirconium oxide adsorbent
CN117551016A
Suspension composition for abrasive cleaning and cleaning of glass surface
JP1996209117A